Organic Reactions 2000
DOI: 10.1002/0471264180.or056.02
|View full text |Cite
|
Sign up to set email alerts
|

The Vilsmeier Reaction of Non‐Aromatic Compounds

Abstract: This chapter extends the discussion to reactions between the Vilsmeier‐Haack reagent (subsequently referred to as the Vilsmeier reagent for brevity) and any other compounds in which a carbon‐carbon bond is formed. The discussion thus excludes reactions in which the Vilsmeier reagent acts as a chlorinating agent (for example in the preparation of acid chlorides), or in which it forms carbon‐oxygen or carbon‐nitrogen bonds, unless these are accompanied by formation of a carbon‐carbon bond. For a discussion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 421 publications
0
44
0
2
Order By: Relevance
“…The formylation of numerous substrates, such as electronrich aromatic or heteroaromatic compounds, [6] as well as electron-rich alkenes and 1,3-dienes, [7] has been achieved by utilizing Vilsmeier reagents (2), which are usually prepared from N,N-disubstituted formamides and acid chlorides (Scheme 2). The relevant works have been well documented in many reviews.…”
Section: Serving As a Precursor In Formylation Reactionsmentioning
confidence: 99%
“…The formylation of numerous substrates, such as electronrich aromatic or heteroaromatic compounds, [6] as well as electron-rich alkenes and 1,3-dienes, [7] has been achieved by utilizing Vilsmeier reagents (2), which are usually prepared from N,N-disubstituted formamides and acid chlorides (Scheme 2). The relevant works have been well documented in many reviews.…”
Section: Serving As a Precursor In Formylation Reactionsmentioning
confidence: 99%
“…[28] To the best of our knowledge, organophosphorus(III) chlorides do not usually react with dimethylformamide.…”
Section: Wwweurjicorg Full Papermentioning
confidence: 99%
“…[11][12][13] Unfortunately, an orienting Vilsmeier-Haak formylation 14 applied to 2-(4-methoxybenzyl)-2,4-dihydro-3H-pyrazol-3-one demonstrated that the PMB group does not survive the harsh conditions of this reaction. For this reason, the more stable but harder to cleave benzyl group and the even less vulnerable methyl group were considered as possible R 1 protecting groups.…”
Section: Methodsmentioning
confidence: 99%